2007
DOI: 10.1038/npre.2007.50.1
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Scriptable Molecular Graphics in Web Browsers without Java3D

Abstract: Jmol is a free, open source molecule viewer for chemistry and biochemistry. It is cross-platform, running on Windows, Mac OS X, and Linux/Unix systems. The software consists of three parts: the JmolApplet is a web browser applet that can be integrated into web pages; the Jmol application is a standalone Java application that runs on the desktop; and the JmolViewer is a development tool kit that can be integrated into other Java applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…Protein structure figures were created using Jmol (http://www.jmol.org), PyMol (http://pymol.org), and MolMol (http://www-theor.ch.cam.ac.uk/IT/software/molmol.html ) [103]–[105]. Some PDB data parsing and protein sequence creation was performed using BioJava 3 (http://www.biojava.org) [106].…”
Section: Methodsmentioning
confidence: 99%
“…Protein structure figures were created using Jmol (http://www.jmol.org), PyMol (http://pymol.org), and MolMol (http://www-theor.ch.cam.ac.uk/IT/software/molmol.html ) [103]–[105]. Some PDB data parsing and protein sequence creation was performed using BioJava 3 (http://www.biojava.org) [106].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis using Jmol software 29 revealed that Gln92 is in close proximity to Glu133 (8.6 Å ), Glu112 (10 Å ), Asp113 (12.7 Å ), and Glu109 (13 Å ). Thus, the formation of a Glu residue at position 92 might be expected to cause significant charge-charge repulsion and potentially to lead to a more open, unfolded tertiary structure.…”
Section: Discussionmentioning
confidence: 99%
“…The electrostatic surface potentials were calculated by solving the linearized PoissoneBoltzmann equation (PBE) with the APBS package (version 1.3) [27]. 3D structures with surface potentials produced by APBS were visualized using Jmol viewer (version 12.0) [28]. The molecular hydrophobic and hydrophilic properties of the predicted models were calculated by the PLATINUM web-server based on the concept of empirical Molecular Hydrophobicity Potential [29].…”
Section: Protein 3d Structure Modelingmentioning
confidence: 99%